Introducing Islamic Values in Early Childhood Education at the Beginning of Schooling - Syifatul Latifah; Betty Handayani; Mu’rifatul Laili; Ika Wulandari; Mohammad Fajar Faizi (Al-Qalam Institute, 2025)
This study aims to examine the efforts to introduce and instill Islamic values in early childhood education during the initial period of school entry at KB Tunas Harapan, Jombang. This research employed a qualitative approach, focusing on observation and documentation as the primary data collection techniques. The findings indicate that the introduction and cultivation of Islamic values in early childhood education at KB Tunas Harapan are implemented through structured school activity management. The achievement of Islamic values education is focused on three main aspects: first, the introduction of aqidah (faith), such as teaching children to recite the two declarations of faith (shahada); second, the introduction of ibadah (worship), including familiarizing children with prayer movements through fasholatan activities; and third, the development of akhlaq (moral conduct) through habituation practices, such as greeting upon entering the classroom and showing respect by kissing the teacher’s hand. This study was conducted at the beginning of the new academic year in the odd semester, with all participants being newly enrolled students who initially had limited understanding of Islamic values. Within a two-week period, early childhood learners at KB Tunas Harapan began to demonstrate positive behavioral changes, such as greeting when entering the classroom. However, some children had not yet fully applied these practices, not due to lack of ability, but rather because they were still shy and adapting to interactions with teachers and peers.